1988
DOI: 10.1002/aja.1001830205
|View full text |Cite
|
Sign up to set email alerts
|

The interdependence of the follicular, parafollicular, and mast cells in the mammalian thyroid gland: A review and a synthesis

Abstract: The aim of this paper is to summarize some of our quantitative descriptive and experimental studies, to discuss them in view of the literature data, and to present a synthesis of the topic. The results of stereological analysis of some tissue components of the rat thyroid gland have been compared with the results of topological studies on the parafollicular cells of various mammalian species. Localization of the parafollicular cells in the central regions of the thyroid gland lobes, where the follicular cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…This hypothesis is supported by different features, such as their characteristic 'parafollicular' position, their predominance in the central region of the thyroid lobe -the so-called "C-cell region" [19]-where the most-active follicles of the gland predominate [20], and their implication in the secretion of many different regulatory factors [1,46,56]. Some of these regulatory peptides display an inhibiting action on thyroid hormone secretion, such as calcitonin, calcitonin gene-related peptide (CGRP) and somatostatin [1], whereas others act as local stimulators of thyroid hormone synthesis, such as gastrin-releasing peptide (GRP), helodermin, and serotonin [35,57,58].…”
Section: Paracrine Role Played By C Cellsmentioning
confidence: 80%
See 1 more Smart Citation
“…This hypothesis is supported by different features, such as their characteristic 'parafollicular' position, their predominance in the central region of the thyroid lobe -the so-called "C-cell region" [19]-where the most-active follicles of the gland predominate [20], and their implication in the secretion of many different regulatory factors [1,46,56]. Some of these regulatory peptides display an inhibiting action on thyroid hormone secretion, such as calcitonin, calcitonin gene-related peptide (CGRP) and somatostatin [1], whereas others act as local stimulators of thyroid hormone synthesis, such as gastrin-releasing peptide (GRP), helodermin, and serotonin [35,57,58].…”
Section: Paracrine Role Played By C Cellsmentioning
confidence: 80%
“…In most species, C cells are located primarily in the centre of thyroid lobes, including humans [15,16], mice [17], rats [18] and rabbits [17]. The area where C cells predominate has been termed as 'C-cell region' [19], which is also the place where the mostactive follicles of the gland predominate [20]. In general, portions of the thyroid containing the highest concentration of C cells correspond to the typical fusion sites of between the UBB and the medial thyroid anlage.…”
Section: Normal Morphology and Distribution Of C Cellsmentioning
confidence: 99%
“…The follicular cell activation index (ia) represents the epithelial volume/colloid volume ratio and indicates the reaction of the thyroid gland structure to the blood TSH concentration [26]. By assuming that the thyroid follicular epithelium can be regarded as forming an approximately hollow sphere, the average follicular epithelium cell height (τ) was calculated as follows: τ = 3Pe × Lt/2Pt × (Ie + Ii + (Ie + Ii) 1/2 ) (Pe = counted points on epithelium, Lt = test line, Pt = total points of the test system, Ie and Ii = external and internal intersections of the structures with the test line, respectively) [27].…”
Section: Animals and Methodsmentioning
confidence: 99%
“…In addition to functional aspects, it has been reported that high levels of TSH cause a hyperplasia of the PF cells (23,24). Similar to the treatment of differentiated thyroid carcinoma, a TSH-suppressive hormone therapy may thus lead to a better prognosis after surgery of an MTC.…”
Section: Introductionmentioning
confidence: 99%